Optimization of substrate preparation for oyster mushroom (Pleurotus ostreatus) cultivation by studying different raw materials and substrate preparation conditions (composting: phases I and II) - Vieira, Fabricio Rocha [UNESP]; Nogueira de Andrade, Meire Cristina [UNESP] (Springer, 2016)
In recent years, oyster mushroom ( Pleurotus ostreatus) has become one of the most cultivated mushrooms in the world, mainly in Brazil. Among many factors involved in a mushroom production, substrate preparation is the most critical step, which can be influenced by composting management techniques. Looking forward to optimizing the substrate preparation process, were tested different composting conditions ( 7 and 14 days of composting with or without conditioning), potential raw materials ( decumbens grass, brizantha grass and sugarcane straw) and nitrogen supplementation ( with or without wheat bran) on oyster mushroom yield and biological efficiency ( BE). The substrate composted for 7 days with conditioning showed higher yield and biological efficiency of mushroom ( 24.04 and 100.54 %, respectively). Substrates without conditioning ( 7 and 14 days of composting) showed smaller mushroom yield and biological efficiency. Among the raw materials tested, brizantha grass showed higher mushroom yield followed by decumbens grass, sugarcane straw and wheat straw ( 28.5, 24.32, 23.5 and 19.27 %, respectively). Brizantha grass also showed higher biological efficiency followed by sugarcane straw, decumbens grass and wheat straw ( 123.95, 103.70, 96.90 and 86.44 %, respectively). Supplementation with wheat bran improved yield and biological efficiency in all substrate formulations tested; thus, oyster mushroom yield and biological efficiency were influenced by substrate formulation ( raw materials), supplementation and composting conditions.
Keywords: Composting; Pleurotus ostreatus; Yield; Supplement; Raw materials